DIVINATION BY TREND SALES WITH STRAIGHT LINES LEAST SQUARE METHOD - Damayanti Sari Dewi; Irfan SKom, MM (Jurnal Sistem Informasi, 2000)
With the sales forecast for the coming year it will be useful for production planning. Ni sales gain forecast in the least squares method in which the square deviation obtained over the minimum in comparison with the free hand or using semi-average method. To obtain the trend values are used Normal Equations I and II, where it has obtained a total number of years equal to 0.